HIFI-α activation underlies a functional switch in the paradoxical role of Ezh2/PRC2 in breast cancer - Mahara, Sylvia; Lee, Puay Leng; Feng, Min; Tergaonkar, Vinay; Chng, Wee Joo; Yu, Qiang (Proceedings of the National Academy of Sciences - PNAS, 2016)
Despite the established oncogenic function of Polycomb repressive complex 2 (PRC2) in human cancers, its role as a tumor suppressor is also evident; however, the mechanism underlying the regulation of the paradoxical functions of PRC2 in tumorigenesis is poorly understood. Here we show that hypoxia-inducible factor 1, α-subunit (HIFI-α) is a crucial modulator of PRC2 and enhancer of zeste 2 (EZH2) function in breast cancer. Interrogating the genomic expression of breast cancer indicates high HIF1A activity correlated with high EZH2 expression but low PRC2 activity in triple-negative breast cancer compared with other cancer subtypes. In the absence of HIFIA activation, PRC2 represses the expression of matrix metalloproteinase genes (MMPs) and invasion, whereas a discrete Ezh2 complexed with Forkhead box M1 (FoxM1) acts to promote the expression of MMPs. HIF1-α induction upon hypoxia results in PRC2 inactivation by selective suppression of the expression of suppressor of zeste 12 protein homolog (SUZ12) and embryonic ectoderm development (EED), leading to a functional switch toward Ezh2/FoxM1-dependent induction of the expression of MMPs and invasion. Our study suggests a tumor-suppressive function of PRC2, which is restricted by HIF1-α, and an oncogenic function of Ezh2, which cooperates with FoxM1 to promote invasion in triple-negative breast cancer.